TI_GERICHTE 11.2013.71 vom 23. Januar 2015 , Ipoteca legale degli artigiani e imprenditori: iscrizione definitiva - TI Tribunale d'appello (2015)
Ipoteca legale degli artigiani e imprenditori: iscrizione definitiva